Biodegradable and adjustable sol-gel glass based hybrid scaffolds from multi-armed oligomeric building blocks. (November 2017) - Kascholke, Christian; Hendrikx, Stephan; Flath, Tobias; Kuzmenka, Dzmitry; Dörfler, Hans-Martin; Schumann, Dirk; Gressenbuch, Mathias; Schulze, F. Peter; Schulz-Siegmund, Michaela; Hacker, Michael C.
Graphical abstract: Abstract: Biodegradability is a crucial characteristic to improve the clinical potential of sol-gel-derived glass materials. To this end, a set of degradable organic/inorganic class II hybrids from a tetraethoxysilane(TEOS)-derived silica sol and oligovalent cross-linker oligomers containing oligo(d, l -lactide) domains was developed and characterized. A series of 18 oligomers (Mn: 1100–3200 Da) with different degrees of ethoxylation and varying length of oligoester units was established and chemical composition was determined. Applicability of an established indirect rapid prototyping method enabled fabrication of a total of 85 different hybrid scaffold formulations from 3-isocyanatopropyltriethoxysilane-functionalized macromers. In vitro degradation was analyzed over 12 months and a continuous linear weight loss (0.2–0.5 wt%/d) combined with only moderate material swelling was detected which was controlled by oligo(lactide) content and matrix hydrophilicity. Compressive strength (2–30 MPa) and compressive modulus (44–716 MPa) were determined and total content, oligo(ethylene oxide) content, oligo(lactide) content and molecular weight of the oligomeric cross-linkers as well as material porosity were identified as the main factors determining hybrid mechanics. Cytocompatibility was assessed by cell culture experiments with human adipose tissue-derived stem cells (hASC). Cell migration into the entire scaffold pore network was indicated and continuous proliferation over 14 days was found. ALP activity linearly increased over 2 weeks indicating osteogenic differentiation. The presented glass-based hybrid concept with precisely adjustable material properties holds promise for regenerative purposes. Statement of Significance: Adaption of degradation kinetics toward physiological relevance is still an unmet challenge of (bio-)glass engineering. We therefore present a glass-derived hybrid material with adjustable degradation. A flexible design concept based on degradable multi-armed oligomers was combined with an established indirect rapid prototyping method to produce a systematic set of porous sol-gel-derived class II hybrid scaffolds. Mechanical properties in the range of cancellous bone were narrowly controlled by hybrid composition. The oligoester introduction resulted in significantly increased compressive moduli. Cytocompatible hybrids degraded in physiologically relevant time frames and a promising linear and controllable weight loss profile was found. To our knowledge, our degradation study represents the most extensive long-term investigation of sol-gel-derived class II hybrids. Due to the broad adjustability of material properties, our concept offers potential for engineering of biodegradable hybrid materials for versatile applications.